PELATIHAN AKUNTANSI JURNAL PENYESUAIAN BAGI SISWA/I SMA RICCI 1 JAKARTA - Hidajat, Nastasya Cindy (Jurnal Serina Abdimas, 2023)
ABSTRACT This Community Service Activity (PKM) is one of the manifestations of the Tri Dharma of Higher Education, to provide benefits to the community. The target of this PKM is training in accounting related to adjusting entries for students of SMA Ricci 1, Jakarta. It is hoped that this training activity will be able to provide benefits for Ricci 1 High School students to understand more about adjusting entries along with how to journalize the transactions so that they can improve their knowledge about accounting cyclic and can be useful in producing financial statement correctly. In addition, it is also hoped that this training will provide benefits for Tarumanagara University, especially the Faculty of Economics and Business, in fostering good relations with schools so that they get a better reputation from schools and students. This training is given to class X and XI students. The training was carried out through the Zoom application with a duration of 50 minutes. The implementation of the activities included the presentation of material by the Untar PKM Team, then continued with practice questions and ended with a question and answer session. During the implementation, it was seen that the students enthusiastically welcomed this training activity. The results of the questionnaire also show that the material presented can increase students' knowledge and increase their interest in the accounting field, and hope to be trained again in the future with different materials. ABSTRAK Kegiatan Pengabdian Kepada Masyarakat (PKM) ini merupakan salah satu perwujudan Tri Dharma Perguruan Tinggi, untuk memberikan manfaat kepada masyarakat. Sasaran PKM ini adalah pelatihan akuntansi terkait penyusunan jurnal penyesuaian kepada siswa SMA Ricci 1, Jakarta. Diharapkan kegiatan pelatihan ini mampu memberikan manfaat bagi siswa SMA Sekolah Ricci 1 untuk lebih memahami mengenai jurnal penyesuaian beserta dengan cara membuat jurnalnya sehingga dapat membekali pengetahuan mereka mengenai siklus akuntansi dan dapat berguna dalam menyusun laporan keuangan secara tepat. Selain itu, diharapkan juga agar pelatihan ini memberikan manfaat bagi Universitas Tarumanagara, khususnya Fakultas Ekonomi dan Bisnis, dalam membina hubungan baik dengan sekolah sehingga mendapatkan reputasi yang semakin baik dari sekolah dan para siswa. Pelatihan ini diberikan kepada siswa kelas X dan XI. Pelaksanaan pelatihan dilakukan melalui aplikasi Zoom dengan durasi 50 menit. Pelaksanaan kegiatan meliputi pemaparan materi oleh Tim PKM Untar kemudian dilanjutkan dengan latihan soal dan diakhiri dengan sesi tanya jawab. Selama pelaksanaan, terlihat para siswa menyambut dengan antusias kegiatan pelatihan ini. Hasil kuesioner juga menunjukkan bahwa materi yang disampaikan dapat menambah pengetahuan siswa dan menambah ketertarikan mereka pada bidang akuntansi, serta berharap untuk kembali mendapatkan pelatihan dengan materi yang berbeda.